The development of C4 rice: current progress and future challenges - von Caemmerer, Susanne; Quick, W. Paul; Furbank, Robert T. (American Association for the Advancement of Science, 2012)
Another “green revolution” is needed for crop yields to meet demands for food. The international C 4 Rice Consortium is working toward introducing a higher-capacity photosynthetic mechanism—the C 4 pathway—into rice to increase yield. The goal is to identify the genes necessary to install C 4 photosynthesis in rice through different approaches, including genomic and transcriptional sequence comparisons and mutant screening.